Antioxidative stress activity of phloroglucinol as a protector against pancreas cell damage in diabetes: In silico and in vivo study - Puspitasari, Renny Novi; Kurnijasanti, Rochmah; I'tishom, Reny; Mustafa, Mohammad Rais; Sudjarwo, Sri Agus (Edelweiss Applied Science and Technology, 2025)
Diabetes is a metabolic disease characterized by hyperglycemia, which can increase oxidative stress and induce pancreatic cell damage. The study's objective was to investigate the in silico and in vivo anti-oxidative stress activity of phloroglucinol as a protector against streptozotocin-induced pancreatic cell damage in mice. Molecular docking of phloroglucinol on the target proteins of the nuclear factor erythroid 2–related factor 2 (Nrf2), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (Cat) was conducted in the in silico study. In rat pancreatic cells stimulated with streptozotocin, in vivo research was conducted to prove the anti-oxidative stress activity of phloroglucinol as a protector against pancreatic cell damage. It was histologically analyzed using hematoxylin and eosin staining. Additionally, blood glucose levels were measured. In the in silico evaluation, phloroglucinol exhibited higher binding energy against Nrf2 (ΔG affinity = -3.8 kcal/mol), SOD (ΔG affinity = -4.2 kcal/mol), GPx (ΔG affinity = -4.1 kcal/mol), and catalase (ΔG affinity = -5.3 kcal/mol). In the in vivo investigation, STZ treatment resulted in morphological abnormalities, pancreatic cell necrosis, and increased blood glucose levels. However, the administration of phloroglucinol prevented the necrosis of pancreatic cells and decreased blood glucose levels. This study shows that phloroglucinol can protect pancreatic cells from oxidative damage through its antioxidant properties, such as SOD, GPx, and catalase. Phloroglucinol exhibited higher binding energy against Nrf2, SOD, GPx, and catalase.